2006
DOI: 10.1002/job.378
|View full text |Cite
|
Sign up to set email alerts
|

Organizational identity strength, identification, and commitment and their relationships to turnover intention: does organizational hierarchy matter?

Abstract: SummaryIn the present study we sought to clarify the functional distinctions between organization identity strength, organizational identification, and organizational commitment. Data were obtained from 10 948 employees of a large steel manufacturer. First, confirmatory factor analysis was used to test the discriminant validity of the three focal constructs. Next, drawing on research that suggests hierarchical differentiation may influence individuals' conceptual frame of reference, we examined each focal cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
238
1
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(276 citation statements)
references
References 60 publications
13
238
1
12
Order By: Relevance
“…Organizational tenure captures the length of the employment relationship, and those with longer tenure have been found to have lower turnover intentions (Rafferty & Griffin, 2006). There is also research evidence that educational level and job level are related to withdrawal intentions (Cole & Bruch, 2006;Grawitch, Trares, & Kohler, 2007;Ng & Feldman, in press). …”
Section: Methodsmentioning
confidence: 99%
“…Organizational tenure captures the length of the employment relationship, and those with longer tenure have been found to have lower turnover intentions (Rafferty & Griffin, 2006). There is also research evidence that educational level and job level are related to withdrawal intentions (Cole & Bruch, 2006;Grawitch, Trares, & Kohler, 2007;Ng & Feldman, in press). …”
Section: Methodsmentioning
confidence: 99%
“…Group members tend to maintain a specific collective identity when social classification makes one group apparently different from other groups [32]. Members with the same collective identity will naturally tend to share the consciousness of this social classification within the same group but refuse to share with other groups [32].…”
Section: Collective Identities and Perceived Crmentioning
confidence: 99%
“…Members with the same collective identity will naturally tend to share the consciousness of this social classification within the same group but refuse to share with other groups [32]. Collective identities always mean specific goals, values, believes, norms, interaction styles and time range [33].…”
Section: Collective Identities and Perceived Crmentioning
confidence: 99%
See 1 more Smart Citation
“…Though no direct evidence exists, indirect evidence indicates that the relationships between constructs could be different based on occupation. For example, previous studies have shown that the relationships Sources of Support 22 between antecedents and organizational commitment and the relationships between organizational commitment and consequences of it differ based on occupations (e.g., Chelte & Tausky, 1986;Cole & Bruch, 2006). Thirdly, the relationships among coworker support, supervisor support, and organizational support should be investigated.…”
Section: Sources Of Support 20mentioning
confidence: 99%